Chemical intervention for enhancing growth and reducing grain arsenic accumulation in rice. (1st May 2021) - Srivastava, Ashish Kumar; Pandey, Manish; Ghate, Tejashree; Kumar, Vikash; Upadhyay, Munish Kumar; Majumdar, Arnab; Sanjukta, Abhay Kumar; Agrawal, Ashish Kumar; Bose, Sutapa; Srivastava, Sudhakar; Suprasanna, Penna
Abstract: Arsenic (As) is a ubiquitous environmental carcinogen that enters the human food chain mainly through rice grains. In the present study, we evaluated the potential of thiourea (TU; non-physiological reactive oxygen species scavenger) in mitigating the negative effects of arsenic (As) stress in indica rice variety IR64, with the overall aim to reduce grain As accumulation. At seedling stage, As + TU treatment induced the formation of more numerous and longer crown roots compared with As alone. The As accumulation in main root, crown root, lower leaf and upper leaf was significantly reduced to 0.1-, 0.14-, 0.16-, 0.14-fold, respectively in As + TU treated seedlings compared with those of As alone. This reduced As accumulation was also coincided with light-dependent suppression in the expression levels of aquaporins and photosynthesis-related genes in As + TU treated roots. In addition, the foliar-supplemented TU under As-stress maintained reducing redox conditions which decreased the rate of As accumulation in flag leaves and, eventually grain As by 0.53-fold compared with those of As treatment. The agronomic feasibility of TU was validated under naturally As contaminated sites of Nadia (West Bengal, India). The tiller numbers and crop productivity (kg seed/ha) of TU-sprayed plants were increased by 1.5- and 1.18-fold, respectively; while, grain As accumulation was reduced by 0.36-fold compared with those of water-sprayed control. Thus, this study established TU application as a sustainable solution for cultivating rice in As-contaminated field conditions. Graphical abstract: Image 1 Highlights: Crown root formation was activated as an adaptive mechanism under arsenic stress. Thiourea supplementation reduced arsenic accumulation from root and leaves. Thiourea downregulated aquaporins and photosynthesis related genes in roots. Thiourea mediated changes coincided with increased salicylic acid accumulation. Foliar-spray of thiourea enhanced yield and reduced grain arsenic accumulation. Abstract : Thiourea supplementation downregulated aquaporins to restrict arsenic accumulation in seedlings. Foliar-applied thiourea enhanced yield and reduced grain arsenic accumulation.